Evaluasi Kinerja Gedung Parkir Sepeda Motor Kampus A Universitas Negeri Jakarta - Nugroho, Oki Prasetyo; Chrisnawati, yusfita; Lenggogeni, Lenggogeni (LPPM Universitas Negeri Jakarta, 2015)
The purpose of the implementation of this study is to provide an evaluation of motorcycle parking building’s performance located on the campus A State University of Jakarta which is locatedon Rawamangun Muka Street, East Jakarta 13220 in order to be considered to fulfill the demand and development of services based on Governor’s Decision of DKI Jakarta, number 42 year 1999 and the Guidelines for Planning and Operation o fparking facilities published bythe Directorate General of Land Transportation DKIJakarta.This research is using a descriptive quantitative and descriptive qualitative survey approach. Like cordoncounts survey, number plate matching survey, direct survey and interviews to knows the parking volume, parking accumulation, parking turnover, parking index, parking facilities and parking management. The population inthis study are all motorcycles that park in the motorcycle parking building on campus A State University of Jakarta. The sample in this study using incidental sampling technique.Based on the researchthat has been done, motorcycle parking building on campus A Jakarta State University just comply 63.6% of the requirements that must be fulfilled, that parking building is also not able to fulfill the parking demand andhas not been used optimally because 5th floor is not used at all. From the interviews, the constraints that faced by managers for handling the motorcycle parking building comes from the pakring user who always against the rules